Loading spectrum for highway bridges and damage criteria for cumulative loading. - Kwok, Chun-Kong. (University of Ottawa (Canada), 1972)
Bridges are presently designed to withstand the bending moments and shear forces produced by a standard design truck such as AASHO H2O-S16. However, bridges are subjected to a large number of loads of different magnitude randomly ordered with respect to time. This thesis describes a literature summary to obtain a description of the magnitude of loads and number of occurrences (load spectrum) on highway bridges. Secondly, the behaviour of bridges under random fatigue load was investigated. From the data obtained at weigh stations of the gross weight and.axle loads of actual trucks, a general description of the load spectrum was obtained. By applying factors to allow for regional trends and local factors a design spectrum could be obtained for any particular bridge. Literature concerning the damage criteria of bridges is very limited and no criteria has been found which satisfactorily summarizes the cumulative damage to bridge materials by random loads.
Keywords: Engineering, Civil.